Revitalisasi Proses Kepemimpinan Birokrasi yang Realistis dan Dinamis - Mulyadi, Deddy (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2006)
Public bureaucracy has to consider the changes of internal and external environmrnt since the development of technology in particular has grown rapidly to fulfill the demand of public needs. It has to improve the quality of service in all aspects. Unfortunately, the bureaucracy cannot fully meet the demand of society because of the number of reasons such as low quality of human resources, inadequate infrastructure including system and procedure. This condition should be improved through among other revitalization of bureaucracy. One of ways in which it can be implemented is to improve the bureaucratic leadership. The leadership capability of apparatus should be developed in order to carry out their daily duties in the institution. Training program is although the implementation is sometimes, it not often, ineffective. However, other alternative solutions can be offered to solve the problem.